(untitled) (Texas Journal of Agriculture and Biological Sciences, 2024)
The article discusses the use of unmanned aerial vehicles (drones) to designate protection zones of hydrographic objects in the context of growing anthropogenic impact on water resources. The advantages of using drones for monitoring, mapping and control of security zones are described, as well as the role of geographic information systems in processing the received data